2022
DOI: 10.1093/pnasnexus/pgac030
|View full text |Cite
|
Sign up to set email alerts
|

The localization of phototropin to the plasma membrane defines a cold-sensing compartment in Marchantia polymorpha

Abstract: Plant cells perceive cold temperatures and initiate cellular responses to protect themselves against cold stress, but which cellular compartment mediates cold sensing has been unknown. Chloroplasts change their position in response to cold to optimize photosynthesis in plants in a process triggered by the blue-light photoreceptor phototropin (phot), which thus acts as a cold-sensing molecule. However, phot in plant cells is present in multiple cellular compartments, including the plasma membrane (PM), cytosol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The distinct localisation of Aephot-Citrine in M. polymorpha could potentially explain why it did not promote the signaling pathway because the avoidance response under cold conditions was reported to be initiated from the photoactivated phot at the plasma membrane. 26,33 Anyway, although cells expressing Aephot-Citrine did not exhibit to promote the signaling pathway (Figure 3A and Table 1), we observed that the plasma membrane-resident Aephot-Citrine in approx. 50% of the cells (Figure S4).…”
Section: Discussionmentioning
confidence: 85%
“…The distinct localisation of Aephot-Citrine in M. polymorpha could potentially explain why it did not promote the signaling pathway because the avoidance response under cold conditions was reported to be initiated from the photoactivated phot at the plasma membrane. 26,33 Anyway, although cells expressing Aephot-Citrine did not exhibit to promote the signaling pathway (Figure 3A and Table 1), we observed that the plasma membrane-resident Aephot-Citrine in approx. 50% of the cells (Figure S4).…”
Section: Discussionmentioning
confidence: 85%
“…Low temperatures can inactivate the functions of the plasma membrane, including destroying its lipid bilayer structure and negating its transport activities as well as basic metabolism [ 38 , 39 , 40 ]. To cope with low-temperature stress, plant membranes have evolved a variety of adaptive mechanisms, including changing their lipid composition and increasing sugar and soluble protein content [ 41 , 42 , 43 ]. In this process, plasma membrane proteins and lipids have been well described [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…To cope with low-temperature stress, plant membranes have evolved a variety of adaptive mechanisms, including changing their lipid composition and increasing sugar and soluble protein content [ 41 , 42 , 43 ]. In this process, plasma membrane proteins and lipids have been well described [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since cold positioning was first described in ferns [ 92 ], researchers have further elaborated on the links between photorelocation and cold acclimation in bryophytes [ 90 , 91 ] and flowering plants [ 90 ]. Phototropins act as thermosensors via blue-light regulated autophosphorylation [ 95 ] and subcellular re-localization [ 96–98 ], modulating the actin-dependent repositioning of chloroplasts as unfused aggregates in response to cold [ 99–101 ]. Seasonal rearrangement of chloroplasts was also observed in the mesophyll of two conifer species, in which chloroplasts move from the periphery along the cell wall in the summer to a more internal location in the cell in the winter ( Figure 1B ), a process that involves the vacuole and cytoplasmic strands [ 102 ].…”
Section: Chloroplastsmentioning
confidence: 99%